Aromacare Melati Meningkatkan Pemenuhan Kebutuhan Tidur pada Lansia - Heri Kusnaidi; Joni Haryanto; Makhfudli Makhfudli (Jurnal Ners, 2011)
Introduction: Sleep disorder is one of the problems that faced by elderly. Progress of sleep change from time to time, sleep patterns during the aging experience different than younger people. Sleep patterns in elderly decreases according with increasing age and degenerative processes that occur in physiological. Aroma of jasmine is the one of method to increase sleep needs, but giving the aroma of jasmine with nursing intervention that called aromacare to reduce sleep disorder is never investigated.Method: This study used quasy experiment pretest and posttest design. The population were elderly with sleep disorder in Tresna Werdha Puspakarma Service Home Elderly Mataram. The samples were recruited using purposive sampling, total samples were 14 respondents, according to inclusion and exclusion criteria. The independent variable was aromacare of jasmine and the dependent variable was sleep in elderly. Data were collected using structure questionnaire. Data were analyzed by using wilcoxon sign rank test and mann whitney test to fulfillment adequacy of sleep based on quantity, paired t test and independent t test to fulfi llment adequacy of sleep on quantity with significance α ≤ 0.05.Result: Result showed that aromacare of jasmine increase of fulfi llment of the need of sleep in quality (p < 0.016) and also effect the need of sleep in quantity (p < 0.001).Discussion: It can be concluded that aromacare of jasmine has significantly effect on sleep need of the elderly. Further research should measure the effect of aromacare of jasmine on fulfillment of the need of sleep with the rate of melatonin and EEG (Electro Encephalo Gram).